Influence of sagittal pelvic attitude on gait pattern in normally developed people and interactions with neurological pathologies: A pilot study - Favetta, Martina; Romano, Alberto; Summa, Susanna; Colazza, Alessandra; Minosse, Silvia; Vasco, Gessica; Castelli, Enrico; Petrarca, Maurizio (Frontiers in Human Neuroscience, 2022)
Background Gait Analysis of healthy people, imitating pathological conditions while walking, has increased our understanding of biomechanical factors. The influence of the pelvis as a biomechanical constraint during gait is not specifically studied. How could mimicking a pelvic attitude influence the dynamic mechanical interaction of the body segments? We proposed an investigation of the pelvic attitude role on the gait pattern of typically developed people when they mimicked pelvic anteversion and posteroversion. Methods Seventeen healthy volunteers were enrolled in this study (mean age 24.4± 5.5). They simulated a pelvic anteversion and posteroversion during walking, exaggerating these postures as much as possible. 3D gait analysis was conducted using an optoelectronic system with eight cameras (Vicon MX, UK) and two force plates (AMTI, Or-6, US). The kinematic, kinetic, and spatio-temporal parameters were compared between the three walking conditions (anteversion, posteroversion, normal gait). Results In Pelvic Anteversion gait (PA) we found: increased hip flexion (p<0.0001), increased knee flexion during stance (p=0.02), and reduction of ankle flexion-extension Range of Motion (RoM) compared with Pelvic Normal gait (PN). In Pelvic Posteroversion gait (PP) compared with PN, we found: decreased hip flexion-extension RoM (p<0.01) with a tendency to hip extension, decreased knee maximum extension in stance (p=0.033), and increased ankle maximum dorsiflexion in stance (p=0.002). Conclusions The configuration of PA contains gait similarities and differences when compared with pathologic gait where there is an anteversion as seen in children with Cerebral Palsy or Duchenne Muscular Dystrophy. Similarly, attitudes of PP have been described in patients with Charcot-Marie-Tooth Syndrome or patients who have undergone pelvic osteotomy. Understanding the dynamic biomechanical constraints is essential to the assessment of pathological behaviour. The central nervous system adapts motor behaviour in interaction with body constraints and available resources.